A COMPARATIVE STUDY ON THE INTERESTS AND VALUES OF INSTITUTIONALIZED CHILDREN AND OF DANCING CHILDREN WHO COME FROM FAMILIES - Gabriela TOMESCU; Monica-Iulia STĂNESCU; Kamer-Ainur AIVAZ (Cluj University Press, 2022)
Introduction: Institutionalized children are at risk in terms of their integration into society, as the lack of educational and financial resources hinders the development of their cognitive and non-cognitive skills. Sports activities contribute to the development of interests and influence the general education of the children, which can be stimulated through music and dance - the most representative artistic field that allows the psychomotor development of children. Objective: The aim of this study is to ascertain the differences between the institutionalized children and the dancers who come from families in terms of their interests and values. Materials and Methods: Fifty-five children aged 11-12 participated in the study, including 30 children in foster care who do not participate in organized extracurricular physical activities and 25 performance dancers who come from organized families. Results: The interest in the various activities in which children are asked to participate is more obvious in dancers, particularly from an artistic and social point of view, and children in foster care are preoccupied with free time and social relations, with authority being the least valued. Conclusions: The influence of dance on children's development can be noticed in the results of the psychological tests assessing their interests and values, which suggest that dancers are more interested in extracurricular activities compared to children in foster care centers and they are more concerned about their future employment situation. Article history: Received 2022 July 23; Revised 2022 August 29; Accepted 2022 August 29; Available online 2022 November 20; Available print 2022 December 20. REZUMAT. Studiu comparativ privind interesele și valorile copiilor instituționalizați și ale copiilor dansatori care provin din familii. Introducere: Copiii instituționalizați reprezintă o categorie cu factor de risc din punct de vedere al integrării în societate, lipsa resurselor educaționale și financiare împiedicând dezvoltarea abilităților cognitive și noncognitive ale acestora. Activitățile sportive contribuie la formarea intereselor și influențează educația generală a copiilor, care poate fi stimulată prin intermediul muzicii și dansului - acesta fiind cel mai reprezentativ domeniu artistic ce permite dezvoltarea psihomotrică a copiilor. Obiectiv: Scopul acestui studiu este de a stabili diferențele dintre copiii instituționalizați și dansatorii proveniți din familii, din punct de vedere al intereselor și valorilor acestora. Materiale și Metode: La studiu au participat 55 de copii cu vârsta cuprinsă între 11-12 ani, incluzând 30 de copii din centre de plasament care nu participă la activități fizice extrașcolare organizate și 25 de dansatori de performanță, proveniți din familii organizate. Rezultate: Interesul pentru diversele activități la care sunt solicitați copiii este mai bine evidențiat la dansatori, în special din punct de vedere artistic și social, iar copiii din centrele de plasament sunt preocupați de timp liber și de relațiile sociale, cel mai puțin apreciind autoritatea. Concluzii: Influența dansului asupra dezvoltării copiilor poate fi observată în urma rezultatelor testelor psihologice de evaluare a intereselor și valorilor, care sugerează faptul că dansatorii sunt mai interesați de alte activități desfășurate în afara orelor de școală comparativ cu copiii din centre, și sunt mai preocupați de viitoarea situație profesională. Cuvinte cheie: Dans, interese, valori, copii instituționalizați.